Bumblebee - Knight, Travis, 1973-; Steinfeld, Hailee; O'Brien, Dylan, 1991-; Theroux, Justin; Cena, John; Paramount Home Entertainment (Firm) (Paramount Home Entertainment, 2019)
Cybertron has fallen. When Optimus Prime sends a transformer to defend Earth, his journey to become a hero begins. Charlie Watson, a teenager trying to find her place in the world, discovers and repairs the battle-scarred robot, who's disguised as a Volkswagen Beetle. As the Decepticons hunt down the surviving Autobots with the help of a secret agency led by Agent Burns, the transformer and Charlie team up to protect the world in an action-packed adventure that's fun for the whole family.
Originally released as a motion picture in 2018.
Wide screen.
Hailee Steinfeld, Dylan O'brien, Justin Theroux, John Cena, Angela Bassett, Pamela Adlon.
Rating: PG-13; for sequences of sci-fi action violence.
DVD, wide screen; Dolby digital 5.1.
English, French or Spanish dialogue; English, French or Spanish subtitles.
Keywords: Transformers (Fictitious characters) -- Drama; Heroes -- Drama; Teenage girls -- Drama; Feature films; Action and adventure films; Science fiction films